Tari Dayak Melihat Dunia Oleh Komunitas Kita Poleng - Ida Ayu Putri Widiastuti; Ni Made Arshiniwati; Yulinis Yulinis (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2023)
Dayak Seeing the World Dance is a contemporary dance project inspired by the Utik river and life on the island of West Kalimantan, one of which is the life of the Iban Dayak Tribe and the Enggang Bird, which is iconic on the island. This work was created as a vehicle to open the world's glasses about the island of Borneo which is actually the lungs of the world, an important message to be conveyed in this project, to the world about the importance of preserving the beauty of nature. The purpose of this study is to explore the meaning of the title of the Dayak Seeing the World dance and the form of its presentation, so as to produce an understanding of the local genius culture that needs to be understood to maintain the traditions of the tribes in the archipelago towards the universal arena. The research method used is descriptive qualitative method to solve problems found in field observations, interviews, literature studies, documentation and apply aesthetic theory and tie hooks to support this paper. The results obtained from this study include: the meaning of the title Dayak Seeing the World which is closely related to the Dayak Tribe as a part of the Primitive Tribes of the State of Indonesia and has factors that influence the Dayak Tribe, such as cultural customs, traditions and cannot be separated from life. nature so far. The form of presentation consists dance moves from the Dayak tribe that were developed and created but did not change their original from, of a contemporary dance form danced by six dancers, fbrown, using Lanjoor Tombak and Mandau properties, red lighting to strengthen the project with a strong and bold by electronic music (MIDI). Keywords: Dayak Dance Seeing the World, Meaning, Form Of Presentation.